Editorial, Seminars in Cell & Developmental Biology - Davis, Frank; Higson, Seamus P. J. (Elsevier, 2009)
It is a pleasure to introduce this special edition of Cell and Development Biology dedicated to the field and application of Biosensors. This edition comprises seven reviews covering the most active research areas where we believe some of the most prominent advances in the field are likely to emerge in the near to medium term. In line with scope of this journal, some emphasis is given towards techniques applicable to Cell Biology.